O PROCESSO DE REUTILIZAÇÃO DA CASCA DO ARROZ: UM ESTUDO DE CASO NA EMPRESA J. FIGHERA & CIA. LTDA - Cechin, Jenesca; Ibdaiwi, Thiago Kader Rajeh; Almeida, Damiana Machado de; Costa, Vania Medianeira Flores; Lopes, Luis Felipe Dias; Santos, Rita de Cássia Trindade dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Although the theme Social and Environmental Responsibility is still challenging, many companies are seeking ways to preserve environmental and ecological in order to stand out in the market. This article presents the process of reuse rice husk in Company J. Fighera & Cia Ltda in Santa Maria - RS. The research is characterized as descriptive nature of literature and case study assumptions. The results prove that the said rice mill is concerned with environmental issues and therefore already adopted measures such as reusing the shell to fire the furnaces of tedder, sell the remaining residue for pottery, pens and aviaries. It is suggested that the company make partnerships with timber industries. We conclude that environmental concern is a fundamental step for any company that wishes effectiveness, organizational excellence and wants to be benchmark in modern society.